2011
DOI: 10.1093/jmt/48.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Feminist Music Therapy Pedagogy: A Survey of Music Therapy Educators

Abstract: This study surveyed 188 music therapy educators regarding their views and use of feminist pedagogy and feminist music therapy. The purpose of this study was two-fold: (a) to determine how many music therapy educators used feminist pedagogy and (b) to determine if there was a relationship between the use of feminist pedagogy and academic rank of the participants. Seventy-two participants responded to this study, with 69 participants included for data analysis. Stake and Hoffman's (2000) feminist pedagogy survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In general, there are few empirical attempts to understand the professional development of students trained in art therapy, music therapy or dance movement therapy (Orkibi, 2013). Educational research in the field of music therapy has specifically included focus on the use of musical instruments and musical skills (Kennedy, 2001;Silverman, 2011), supervision (Forinash, 2001;Tanguay, 2008), clinical practice development (Madsen & Kaiser, 1999;Wheeler, 2002), models for self-experiential learning and psychotherapy in education (Gardstrom & Jackson, 2011;Murphy, 2007;Scheiby & Pedersen, 1999), reflexive journaling (Barry & O'Callaghan, 2008) and research on feminist pedagogy in music therapy (Hahna & Schwantes, 2011). Role-play as a form of learning in music therapy education is associated with various domains, such as preparation for practicum placements or in the supervision of practice (Goodman, 2011;Murphy, 2007;Tims, 1989).…”
Section: Role-play In Music Therapy Research and Educationmentioning
confidence: 99%
“…In general, there are few empirical attempts to understand the professional development of students trained in art therapy, music therapy or dance movement therapy (Orkibi, 2013). Educational research in the field of music therapy has specifically included focus on the use of musical instruments and musical skills (Kennedy, 2001;Silverman, 2011), supervision (Forinash, 2001;Tanguay, 2008), clinical practice development (Madsen & Kaiser, 1999;Wheeler, 2002), models for self-experiential learning and psychotherapy in education (Gardstrom & Jackson, 2011;Murphy, 2007;Scheiby & Pedersen, 1999), reflexive journaling (Barry & O'Callaghan, 2008) and research on feminist pedagogy in music therapy (Hahna & Schwantes, 2011). Role-play as a form of learning in music therapy education is associated with various domains, such as preparation for practicum placements or in the supervision of practice (Goodman, 2011;Murphy, 2007;Tims, 1989).…”
Section: Role-play In Music Therapy Research and Educationmentioning
confidence: 99%
“…Music therapy work building on this since has included a collection of writings representing diverse understandings of feminisms and touching upon such areas as theory, practice, research, supervision, and pedagogy (Hadley, 2006). Further works have included feminist music therapy practice with survivors of violence (Curtis, 2007(Curtis, , 2008(Curtis, , 2012Curtis & Harrison, 2006), a feminist approach to the Bonny Method of Guided Imagery and Music (BMGIM) (Hahna, 2004), feminist music therapy pedagogy (Hahna, 2010(Hahna, , 2011Hahna & Schwantes, 2011), and feminism and anti-oppressive practice in music therapy (Baines, 2012).…”
Section: Women's Issues and Music Therapists: A Look Forwardmentioning
confidence: 99%
“…A survey has since been conducted, however, of American music therapy educators, examining their views and use of feminist pedagogy and feminist music therapy (Hahna & Schwantes, 2011). Results indicated that a majority (67%, n= 32) used "methods congruent with feminist pedagogy, however, most music therapists did not identify themselves as being feminist music therapists" (p. 307).…”
Section: Women's Issues and Music Therapists: A Look Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, slow music stimulates the parasympathetic nerves and stabilizes the autonomic nervous system [ 21 ]. Thus far, however, previous studies on listening to music for stress relief have been limited to the use of existing sound sources, such as classical music [ 22 ], relaxation music [ 23 ], white noise [ 24 ], or preferred music [ 25 ]. Moreover, most research and design processes to verify the effects of music listening on stress are limited to pre- and post- experimental treatment comparisons, which does not indicate the time series effect of the intervention.…”
Section: Introductionmentioning
confidence: 99%